On liturgical notations in Slavic hagiographic miscellanies - Викторовна Пак, Наталья (Slavistica Vilnensis, 2004)
The article offers a systematization of liturgical notations that appear in Slavic hagiographic miscellany manuscripts. These notations, which are unconnected with the content of the hagiographic texts, indicate that these texts were read during the liturgy, which may be of importance in two respects. First, together with actual liturgical books, these notations can serve as sources on the history of the Slavic liturgy: in particular, they can cast light on how liturgical instructions for reading saints’ lives during matins were carried out in practice. Second, the liturgical text division of saints’ lives, in those cases where such division is made, must be taken into account in the textological study of individual texts.